Study of the influence of the phase composition and crystal structure of FexNi100-x nanostructures on the efficiency of using lithium ion batteries as anode materials - Borgekov, D; Hlebnikov, N. A.; Shlimas, D. I.; Kozlovskiy, A. L. (Eurasian Journal of Physics and Functional Materials, 2026)
The results of the efficiency of using Fe x Ni 100x nanotubes as anode materials for lithium-ion batteries have been obtained. In the course of research, it was found that an increase in the concentration of nickel in the structure to 40 and 60 at.% leads to a sharp increase in the resource number of cycles by more than two times in comparison with iron nanotubes. Such a difference in the resource lifetime is due to the higher stability of Fe x Ni 100x nanotubes with a nickel concentration of more than 40 at.% to destruction, as well as resistance to oxidation. Recommended Citation Borgekov, D. B.; Hlebnikov, N. A.; Shlimas, D. I.; and Kozlovskiy, A. L. (2020) "Study of the influence of the phase composition and crystal structure of FexNi100-x nanostructures on the efficiency of using lithium ion batteries as anode materials," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 4, Article 4. DOI: https://doi.org/10.29317/ejpfm.2020040404